Altered Gut Microbial Load and Immune Activation in a Drosophila Model of Human Tauopathy - Rydbom, Jerrik; Kohl, Halea; Hyde, Vanesa R.; Lohr, Kelly M. (Frontiers in Neuroscience, 2021)
Tau is a microtubule-associated protein that stabilizes the neuronal cytoskeleton. In the family of neurodegenerative diseases known as tauopathies, including Alzheimer’s disease (AD), frontotemporal dementia (FTD), and chronic traumatic encephalopathy (CTE), abnormal tau aggregation destabilizes microtubule structure, contributing to a cascade of cellular processes leading to neuronal cell death. The gut microbiome has increasingly become a target of neurodegenerative disease research since gut microbiome imbalances have been linked to protein aggregation and inflammation through a bidirectional axis linking the gut and brain. Accordingly, the present study examined tau-mediated changes to gut microbiome composition and immune activation in a Drosophila melanogaster model of mutant human tauopathy. Fecal deposit quantification and gastric emptying time courses suggested an abnormal food distribution and reduced gut motility in tau transgenic flies compared to controls. Tau transgenic flies also showed an increase in gut bacteria colony forming units (CFUs) from diluted fly homogenate, indicating an increased bacterial load. Finally, we showed that tau transgenic flies have elevated systemic levels of antimicrobial peptides targeting gram-negative bacteria using qPCR, suggesting an enhanced innate immune response to bacterial insult. These data demonstrate qualifiable and quantifiable gut microbial and innate immune responses to tauopathy. Furthermore, these results provide a framework for future studies targeting the gut microbiota as a modifier of neurodegenerative disease, which would suggest microbiota as a secondary contributor to tau-mediated neurodegeneration.